Nosečnost in porod dvojčkov po postopku IVF-ET - Korošec, Sara (Medicinski razgledi, 1999)
A comparative study of singleton pregnancies after an IVF procedure revaled nosignificant differences in the course or outcome of pregnancy. On the other hand, multiple pregnancy itself is a risk factor for the course and oucome of pregnancy and birth. Since it is approximately twenty times more frequent in medically assisted than in natural conception and therefore constitutes one ofthe major problems of IVF pregnancy and birth. The aim of our research was to determine whether the course and obstetric outcome of twin IVF pregnancy differs from those in natural conception. This retrospective study included 731 women with twin pregnancies who gave birth to twins between April 1987 andMay 1995. We studied 94 twin pregnancy mothers and 188 newborns conceived by an IVF procedure. The research project was divided into a cohort and control study. In the former, the study group was compared to the entire Ljubljana cohort of 637 mothers with twin pregnancy and 1274 newborns born after natural conception. In the control study, we compared the study group to93 twin pregnancy mothers and 186 newborns born after natural conception. Women in the study group and control group were matched for age, parity and birth year. The course and complications of pregnancy, the course, complications and outcome of birth, and the characteristics of newborns were analysed. The incidence of severe complications of pregnancy, such as hypertension, eclampsy, polysymptomatic gestosis, gestation diabetes and threatened preterm labour, in the IVF group of mothers with twin pregnancy didnot exceed that in the control group. (Abstract truncated at 2000 characters)
Keywords: Fertilization in vitro; human pregnancy; nosečnost; porod; childbirth; Embryo transfer; dvojčki; Twins; zunajtelesna oploditev; Pregnancy, multiple; Ovulation induction; Pregnancy; Infant, newborn; Pregnancy complications; Labor; Gestational age; Birth weight